Pre-weaning performance evaluation of a multibreed Aberdeen Angus × Nellore population using different genetic models - Lopes,Jader Silva (2010)
This work aimed at estimating the genetic effects that affect the pre-weaning performance of animals from multibreed crosses. In order to do so, it was used information of the weight at weaning of 79,521 animals, sired by 1,020 bulls and 61,898 cows from Aberdeen Angus and Nellore breeds and from many genetic groups resulted from their crosses. Five genetic models were tested: model 1, containing the fixed breed genetic effects (additive direct and maternal effects, heterozygote direct and maternal effects, epystatic direct and maternal effects, joint additive direct and maternal effects); model 2, equal to model 1, excluding direct and maternal joint additive effects; model 3, equal to model 1, excluding direct and maternal epystatic effects; model 4, equal to model 1, excluding direct and maternal epystactic effect and direct and maternal joint additive effects; and model 5, equal to model 1, excluding direct and maternal heterozygotic effects, direct and maternal epystatic effects and direct and maternal joint additive effects. The models were analyzed by the following methods: least square means method, ridge regression method, and the restricted maximum likelihood method. The dominant additive models usually used for genetic evaluations do not give a good description of the pre-weaning performance variations, making it necessary to add the heterozygote and epystatic effects; the joint additive effects do not significantly improve the adjustment of the analysis model and the heterozygote effects are efficient in representing a quadratic breed additive effect, in addition to insert an unnecessary bias assigned to multicollinearity related to the joint additive effects.